A new map of North America from the latest authorities. - Cary, John, ca. 1754-1835 (J. Cary, 1806)
Map shows Central and North American Pacific coast line; the Atlantic coast line from Labrador to the Canada; United States settlements; Mexican coastal and interior settlements; the West Indies, Iceland, and Greenland. Includes some notes and dates of exploration. Relief shown pictorially. Scale not given.